Identification of direct transcriptional target genes of ExoS/ChvI two-component signaling in Sinorhizobium meliloti - Chen, Esther J; Fisher, Robert F; Perovich, Virginia M; Sabio, Erich A; Long, Sharon R (Journal of bacteriology, 2009)
The Sinorhizobium meliloti ExoS/ChvI two-component signaling pathway is required for the development of a nitrogen-fixing symbiosis between S. meliloti and its plant hosts. ExoS/ChvI also has important roles in regulating succinoglycan production, biofilm formation, motility, nutrient utilization, and the viability of free-living bacteria. Previous microarray experiments with an exoS96::Tn5 mutant indicated that ExoS/ChvI influences the expression of a few hundred genes, complicating the investigation of which downstream genes respond directly or indirectly to ExoS/ChvI regulation. To focus our study of ExoS/ChvI transcriptional target genes, we performed transcriptional profiling with chvI gain-of-function and reduced-function strains. The chvI gain-of-function strain that we used contains a dominant gain-of-function chvI allele in addition to wild-type chvI. We identified genes that, relative to their expression level in the wild type, are both upregulated in the chvI gain-of-function strain and downregulated in the reduced-function strain or vice versa. Guided by this focused set of genes, we performed gel mobility shift assays and demonstrated that ChvI directly binds the intergenic regions upstream of ropB1, SMb21440, and SMc01580. Furthermore, DNase I footprint analysis of the region upstream of SMc01580 identified a specific DNA sequence bound by ChvI and allowed the discovery of a possible motif for ChvI binding. Our results provide insight into the mechanism of how ExoS/ChvI regulates its downstream targets and lay a foundation for studying this conserved pathway with critical roles in free-living and symbiotic bacteria.